The Effectiveness Of Local Wisdom-Based LKPD In Improving Algebraic Numeracy Literacy Of Students At SMPN Kab. Sigi - Hajerina, Hajerina; Mailili, Wahyuni H. (Koordinat Jurnal MIPA, 2025)
This study aims to examine the effectiveness of Student Worksheets (LKPD) based on local wisdom in improving students' numeracy literacy in the subject of Two-Variable Linear Equation Systems (SPLDV). This study uses an pre-experimental design with pre-tests and post-tests to measure students' numeracy literacy. A total of 90 students from 3 public junior high schools in Sigi Regency participated in this study, which were selected through purposive sampling. The instruments used to collect data were tests, questionnaires, and interviews, which were then analyzed using qualitative analysis for questionnaires and interviews and quantitative analysis for test instruments. The results showed a significant increase in post-test scores, with an average pre-test score of 42.86 and a post-test score of 84.17. Data analysis showed an effect size of 2.06, which is classified as very large, indicating a strong impact of the use of local wisdom-based LKPD in improving students' numeracy literacy. In addition, the results of the student response questionnaire showed that the majority of students (80%) felt that LKPD based on local wisdom helped them understand SPLDV material better and made learning more interesting and relevant to their lives. This study concludes that LKPD based on local wisdom is effective in improving students' numeracy literacy and can be an attractive and contextual learning alternative in areas with rich local cultures, with the hope that it can be used as a reference for teachers in designing more contextual mathematics learning tools.